2012
DOI: 10.1186/1743-0003-9-48
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the brain activation induced by functional electrical stimulation and voluntary contraction using functional magnetic resonance imaging

Abstract: BackgroundTo observe brain activation induced by functional electrical stimulation, voluntary contraction, and the combination of both using functional magnetic resonance imaging (fMRI).MethodsNineteen healthy young men were enrolled in the study. We employed a typical block design that consisted of three sessions: voluntary contraction only, functional electrical stimulation (FES)-induced wrist extension, and finally simultaneous voluntary and FES-induced movement. MRI acquisition was performed on a 3.0 T MR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 26 publications
6
25
0
1
Order By: Relevance
“…Neuroimaging studies using fMRI have reported that NMES‐evoked wrist extension movements activate a bilateral region of subcortical and cortical sensorimotor regions (Blickenstorfer et al ., ; Iftime‐Nielsen et al ., ; Joa et al ., ). In the present and previous (Muthalib et al ., ) fNIRS studies, the O 2 Hb‐ and HHb‐derived bilateral cortical sensorimotor activation profile induced by unilateral NMES of the wrist extensors is in agreement with these previous fMRI findings.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Neuroimaging studies using fMRI have reported that NMES‐evoked wrist extension movements activate a bilateral region of subcortical and cortical sensorimotor regions (Blickenstorfer et al ., ; Iftime‐Nielsen et al ., ; Joa et al ., ). In the present and previous (Muthalib et al ., ) fNIRS studies, the O 2 Hb‐ and HHb‐derived bilateral cortical sensorimotor activation profile induced by unilateral NMES of the wrist extensors is in agreement with these previous fMRI findings.…”
Section: Discussionsupporting
confidence: 64%
“…NMES induces CNS effects by enhancing voluntary motor control (Knutson et al ., ). Increased proprioceptive and cutaneous afferent signals (from the NMES electric field directly activating peripheral sensory nerves and from NMES‐evoked movements) send signals to subcortical and cortical bilateral sensorimotor regions, particularly the contralateral sensorimotor region (Blickenstorfer et al ., ; Iftime‐Nielsen et al ., ; Joa et al ., ; Muthalib et al ., ), which was confirmed by the present study. Furthermore, the ipsilateral sensorimotor region activation elicited by unilateral NMES‐evoked wrist extension movements indicated that there were transcallosal interactions between the two hemispheres (Iwamura, ; Maffiuletti et al ., ; Muthalib et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortical correlates of NMES-evoked movements have been demonstrated in a few functional magnetic resonance imaging (fMRI) studies [ 10 14 ]. For instance, Blickenstorfer et al (2009) observed a cortical activation pattern including the contralateral primary motor (M1) and sensory (S1) cortex (i.e., sensorimotor cortex-SMC) and bilateral secondary somatosensory area (S2), supplementary motor area (SMA), premotor cortex (PMC), and regions of the prefrontal cortex (PFC) during NMES-evoked wrist extension/flexion movements at current intensities just above the individual motor threshold (9–23mA) but minimising pain discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, individuals with SCI that preserve small motor responses might be benefited from the use of FES. This can be explained by the fact that when the individual has the ability to perform concurrent voluntary contraction to the FES, the final motor response can be more effective and coordinate than when only FES application occurs (Joa et al, 2012).…”
Section: Discussionmentioning
confidence: 99%